2005
DOI: 10.1038/sj.onc.1208692
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression responses to DNA damage are altered in human aging and in Werner Syndrome

Abstract: The accumulation of DNA damage and mutations is considered a major cause of cancer and aging. While it is known that DNA damage can affect changes in gene expression, transcriptional regulation after DNA damage is poorly understood. We characterized the expression of 6912 genes in human primary fibroblasts after exposure to three different kinds of cellular stress that introduces DNA damage: 4-nitroquinoline-1-oxide (4NQO), c-irradiation, or UV-irradiation. Each type of stress elicited damage specific gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Gene expression profiling in WS closely resembles that of normal aging, suggesting that the transcription alterations common to WS and normal aging represent general events in the aging process [5]. Cells from WS and old individuals had similarly aberrant transcriptional responses to IR (ionizing radiation) and UV irradiation, suggesting a role for WRN in stress-induced gene expression [6]. The cellular studies clearly indicate that WS has multiple deficiencies and the WRN gene product is likely to have pleiotropic functions in vivo.…”
mentioning
confidence: 94%
“…Gene expression profiling in WS closely resembles that of normal aging, suggesting that the transcription alterations common to WS and normal aging represent general events in the aging process [5]. Cells from WS and old individuals had similarly aberrant transcriptional responses to IR (ionizing radiation) and UV irradiation, suggesting a role for WRN in stress-induced gene expression [6]. The cellular studies clearly indicate that WS has multiple deficiencies and the WRN gene product is likely to have pleiotropic functions in vivo.…”
mentioning
confidence: 94%
“…These opposing actions have indicated that senescence is a 'double-edged sword', in that senescence acts as a tumor suppressor mechanism to directly prevent cancer, yet potentially enhances cancer via the action of senescent cell products (34). Prior studies have shown that WS cells have gene expression patterns that are characteristic of control senescent cells even when they are not actually senescent (35,36). We obtained suggestive but not definitive evidence that, as they reach crisis, tumor cells derived from WS fibroblasts may be more malignant than those from control fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic resemblance of WS to precocious aging has often begged the question of how closely WS is related to normal aging processes. Recent microarray studies have indicated that gene expression patterns are similar between WS cells and those from aged individuals after exposure to gamma and UV radiation, suggesting similarities in cellular microenvironments [41]. The diverse roles of WRN and the deleterious effects induced in its absence have prompted several groups to investigate whether allelic variants in WRN are associated with aging-related afflictions in the general population.…”
Section: Progeroid Syndromes Caused By Defects In Dna Helicases/dna Rmentioning
confidence: 99%